Solvent Effects on Thiol-Ene Kinetics and Reactivity of Carbon and Sulfur Radicals - FINDIK, VOLKAN (AMER CHEMICAL SOC, 2020)
The thiol-ene reaction is one of the fundamental reactions in biochemistry and synthetic organic chemistry. In this study, the effect of polar media on the reaction kinetics is taken into account by using the transition state theory; the reactivities of the carbon and sulfur radicals have also been rationalized by using conceptual DFT. The results have shown that the solvents have more impact on hydrogen atom transfer reactions and the chain transfer rate constant, k(CT), can be increased by using nonpolar solvents, while propagation reactions are less sensitive to media. Similarly, the k(P)/k(CT) ratio can be manipulated by changing the environment in order to obtain tailor-made polymers. Regarding the DFT descriptors, the local and global electrophilicity indices are well correlated with the propagation rate constant k(P), whereas the global electrophilicity index is associated with the chain transfer rate constant k(CT). Overall, electrophilicity indices can be used with confidence to predict the kinetics of thiol-ene reactions.
Keywords: CLICK-CHEMISTRY; ENERGIES; ELECTROPHILICITY; POLYMER; RATES; PHOTOPOLYMERIZATION; POLYMERIZATIONS; STABILIZATION; PREDICTION; DENDRIMERS